Joint associations of poor diet quality and prolonged television viewing time with abnormal glucose metabolism in Australian men and women - Reeves, M.; Healy, Genevieve; Owen, N.; Shaw, J.; Zimmet, P.; Dunstan, D. (2013)
Objective: To examine the independent and joint associations of diet quality and television viewing time with abnormal glucose metabolism (AGM) in men and women. Method: Cross-sectional data from 5346 women and 4344 men from the 1999 to 2000 Australian Diabetes, Obesity and Lifestyle Study were examined. Diet quality scores were derived from a food frequency questionnaire and categorised into tertiles (high; moderate; low). Television viewing time was dichotomised into low (= 14. h/week) and high (> 14. h/week). AGM was defined as impaired fasting glucose, impaired glucose tolerance, known or newly diagnosed diabetes based on an oral glucose tolerance test. Regression analyses were adjusted for confounding variables. Results: Diet quality and television viewing time were significantly associated with AGM in women, independent of waist circumference. Compared to women with high diet quality/low television viewing time, women with low diet quality/low television viewing time and women with low diet quality/high television viewing time were significantly more likely to have AGM. Associations were not observed in men. Conclusions: Both poor diet quality and prolonged television viewing should be addressed to reduce risk of AGM in women. Further understanding of modifiable risk factors in men is warranted. © 2013 Elsevier Inc.